1994
DOI: 10.1080/00288330.1994.9516614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of riparian willow trees(Salix fragilis)on macroinvertebrate densities in two small Central Otago, New Zealand, streams

Abstract: The effects of an introduced willow tree species (Salix fragilis) on the densities of macroinvertebrates were examined in two Central Otago, New Zealand, streams during 1991. Significantly lower invertebrate densities and biomass were observed in willow-lined sections of the streams than in nearby open sections in summer, autumn, and winter. This result was observed in riffles and pools, for most dominant species and nearly all functional feeding groups. The effect was not associated with differences in the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 27 publications
2
58
0
1
Order By: Relevance
“…Some studies suggested that invasive species can cause alterations at different levels in the structure and functioning of ecosystems (Ehrenfeld 2010). Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that invasive species can cause alterations at different levels in the structure and functioning of ecosystems (Ehrenfeld 2010). Moreover, the establishment of exotic riparian plants can alter the exchange of organic material between terrestrial and lotic ecosystems, both changing the quantity (Mineau et al 2011(Mineau et al , 2012 or the quality (B€ arlocher & Graça 2002) of terrestrial litter inputs, leading to alterations in the composition (Serra et al 2013) and density (Lester et al 1994) of benthic assemblages. Many studies have shown that, for instance, the introduction and spread of Eucalyptus globulus plantations in Spain had a strong effect on in-stream terrestrial detritus colonization and degradation (Chauvet et al 1997;Pozo et al 1998;Ferreira et al 2006), while other studies have shown weak influence of exotic species on streams (Braatne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This may be brought about by shade decreasing secondary production and invertebrate densities (e.g., Allen 1951;Hopkins 1976;Behmer & Hawkins 1986). However, Lester et al (1994) found that the effect of shading by willows on macroinvertebrate abundance and biomass was not associated with differences in the amount of fine particulate organic layer matter, stone surface organic layer biomass, or chlorophyll a concentration. Likewise, large seasonal increases in coarse particulate organic matter (CPOM) resulting from leaf fall, did not result in an increase in the abundance or biomass of shredders in the macroinvertebrate communities of two streams studied by Lester et al (1994).…”
Section: Introductionmentioning
confidence: 93%
“…For example, OGrady (1993) reported that the cover of aquatic vegetation was reduced by 60% in stream sections flowing under a complete conifer canopy compared to those measured in adjacent open streams. Lester et al (1994) showed that where the riparian willow canopy in a New Zealand stream reduced the incident illumination by up to 80%, the macro invertebrate abundance and biomass was just half that recorded in open streams. However, Glova and Sagar (1994) studied the effects of different levels of shade on three New Zealand streams and showed that the biomass and diversity of benthic invertebrates, as well as the abundance and biomass of brown trout, tended to be higher in moderately shaded stream sections compared with those with dense willow shading or open areas.…”
Section: Buffer Structurementioning
confidence: 99%